Evaluation Of Patient Safety Policy To Nurse In Anutapura General Hospital Palu City - Napirah, Muh. Ryman; Salmawati, Lusia; Rahmi, Andi (Preventif : Jurnal Kesehatan Masyarakat, 2019)
Patient safety in the hospital is a system where the hospital makes the nurture of the patients safer which includes risk assessment, identification and management of patient-related risks. Patient safety problems in general in Anutapura Palu General Hospital are the occurrence of mismanagement by officers, including errors in discipline, communication, to technical errors.This research aimed to evaluate the implementation of patient safety policies for nurses at Anutapura Public Hospital at Palu. This research was quantitative in nature, as many as 72 respondents by using the Slovin formula. The results showed that the variable results in this research were input with value frequency of ≥50 % respondents who stated the good input. Process variables in this research were obtained from the value that in the process it was quite good seen from the value the frequency of ≥50 % respondents who stated that the process was good. The results of the analysis of variable output with value frequency of≥50 % respondents who stated that the output was good. The conclusion that can be drawn is that the results of the evaluation of the implementation of patient safety policies have been applied in Anutapura Public Hospital at Palu. It is expected that the hospital performs performance evaluation and monitoring complaints as well as satisfaction of service users on a regular basis in order todevelop the satisfaction of service users and the community.